2000
DOI: 10.1093/jnen/59.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Tau Pathology in Nerve Cells, Astrocytes, and Oligodendrocytes of Aged Baboons

Abstract: Intracellular filamentous inclusions containing abnormally phosphorylated tau protein are hallmarks of several human neurodegenerative disorders. This study reveals tau-positive cytoskeletal abnormalities in neurons and glial cells of aged baboons. The brains of four baboons (Papio hamadryas, 20-30 yr of age) were examined using the Gallyas silver technique for neurofibrillary changes and phosphorylation-dependent anti-tau antibodies (AT8, AT100, AT270, PHF-1, TG-3). Conspicuous changes were noted in two anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 62 publications
3
56
0
Order By: Relevance
“…(Delacourte et al, 2002(Delacourte et al, , 2003. Recently, several authors reported an age-dependent pattern of glial tau aggregation in both human and baboon brains (Schultz et al, 2000;Yang et al, 2005b). Previous studies have shown that hyperphosphorylation of tau occurs in the brain of SAMP8 mice at 5 months of age (Canudas et al, 2005;Sureda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(Delacourte et al, 2002(Delacourte et al, , 2003. Recently, several authors reported an age-dependent pattern of glial tau aggregation in both human and baboon brains (Schultz et al, 2000;Yang et al, 2005b). Previous studies have shown that hyperphosphorylation of tau occurs in the brain of SAMP8 mice at 5 months of age (Canudas et al, 2005;Sureda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…An age-dependent increase in the phosphorylation of TAU and the formation of neurofibrillary tangles has, for example, been observed in aged bears (Cork et al, 1988), sheep, goats (Braak et al, 1994), bison (Härtig et al, 2000), mouse lemurs (Bons et al, 1995), baboons (Schultz et al, 2000) and various other mammals (Härtig et al, 2001).…”
Section: Tau Hyperphosphorylationmentioning
confidence: 99%
“…35,63,135,152,160,161 Typically these tau changes tend to be sporadic and do not adopt the full blown features of intracellular NFTs and are usually not associated with neuronal loss. Interestingly, even in nonhuman primates, which display substantial plaques formation and tau proteins with highly conserved amino acid sequences, NFT are rarely observed.…”
Section: Neuronal Lesionsmentioning
confidence: 99%